Epidemiology of Malaria Cases, Sunyani Municipality, Ghana, 2020 - Abdul Gafaru Mohammed; Christopher Sunkwa Tamal; Magdalene Akos Odikro; Charles Lwanga Noora; Prince Romeo Quarshie; Edwin Andrew Afari; Ernest Kenu (Journal of Interventional Epidemiology and Public Health)
Introduction: Malaria is endemic in Ghana, accounting for about 40% of all Outpatient Department (OPD) diagnoses. Data on malaria is routinely collected as part of the IDSR monthly reporting forms. Sunyani municipality recorded 56,540 malaria cases in 2016 with about 35% of the cases occurring in children under five years of age. We analyzed malaria surveillance data to identify the distribution of malaria cases by person, place, and time and determine the timeliness and completeness of malaria report submissions in the municipality. Methods: We analyzed malaria surveillance data in Sunyani municipality reported between 2015 and 2019 from the District Health Information Management System (DHIMS 2). We calculated morbidity and mortality rates of cases by person and estimated the proportion of cases by sub-districts. We performed trend analysis and calculated disease threshold levels. We presented the findings using tables and figures. Results: Of 639,361 malaria cases suspected, 93.5% (597512/639361) were tested, of which 49.4% (295458/597512) were positive. Females accounted for 55.7% (164436/295458) of confirmed cases. Children under 5 years recorded the highest proportion, 29.9% (88135/295458) of cases in the municipality. The case fatality rate was 3.7% (18/484) and 1.4% (7/484) for persons under five years and five or more years, respectively. Abesim subdistrict (6276.03 per 10000) recorded the highest number of cases, and the lowest case count was in New Dormaa subdistrict (1890.97 per 10000). The majority of malaria cases were in May and October of each year. Antwi-krom subdistrict recorded the highest rates of report completeness and timeliness at 41.9% and 40.0% respectively. Conclusion: More females were diagnosed with malaria and children <5 years recorded the highest proportion of cases in the municipality. Abesim recorded the highest proportion of malaria cases during the period. High patterns of malaria transmission occurred during months of high rainfall. None of the sub-districts met the World Health Organization (WHO) target for timeliness and completeness of report submission. The National Malaria Elimination Programme (NMEP) should consider interventions such as Seasonal Malaria Chemoprevention (SMC) among children under five, in the municipality.